Delayed Graft Dislocation After Thoracic Aortic Endovascular Repair - Piffaretti, G; Negri, S; Ferraro, S; Bossi, M; Rivolta, N; Fontana, F; Castelli, P (Kathmandu University Medical Journal, 2015)
Background Endograft dislocation in thoracic aorta has not been widely studied.Objectives The purpose of this study is to analyze the incidence and predisposing factor in a single centre experience after 117 procedures.Method Between November 2000 and December 2011, all consecutive patients undergoing endovascular repair for descending thoracic or thoraco-abdominal aortic disease were identified. Follow-up imaging protocol included triple-phase CT-angiography at 1, 4, and 12 months, and annually thereafter. Migration was defined as proximal/ distal movements >10 mm relative to anatomical landmarks or any movement leading to symptoms or reintervention.Result We identified 117 patients. Mean follow-up was 32 months (range, 1-144). Overall, five (4.3%) patients with thoracic EG dislocation were identified. Dislocation was classified as collapse/infolding in 3 cases and migration in 2. Mean delay of the dislocation was 12.7 months. Only one patient developed symptoms and required an additional endograft. In the group of dislocated endografts, mean age (53 ± 20 vs. 68 ± 15, P = .032) and the diameter of the aortic lesion were lower (4.1cm ± 1.6 vs. 5.6cm ± 1.8, P = .069), and the proximal landing zone at “zones 2 and 3” were more frequently used (5 vs. 65, P = 0.81). All but one patient with collapse/infolding are still alive and doing well at a mean follow-up of 80 months.Conclusion Dislocation is an infrequent complication, but not so rare. Young age, small aortic diameter , and proximal sealing at the distal arch were the most important data associated with this complication.Kathmandu University Medical Journal Vol.12(2) 2014: 97-100